Positivity in Action: Character Education through the Positivity Project - Garwood, Justin D (International Journal of Emerging Trends in Social Sciences, 2022)
Recently, a new program – The Positivity Project (P2; https://posproject.org/) – has been developed to address key implementation challenges for teachers. P2 is a professional development program focused on teacher’s use of project-based learning and a universal student character education curriculum that provides educators and students with tools to support socio-emotional skills through daily, 15-minute learning modules across the school year. In this article, we (a) explain the theory informing P2, (b) detail key implementation components, (c) include real-life accounts from students and teachers using P2 across K-12 and alternative settings, and (d) provide suggestions for evaluating the impact of P2 for those schools considering implementation. The P2 program is informed by positive psychology, a strengths-based approach to instruction that is well-suited to support students with disabilities. Currently, there is promising evidence of P2 effectiveness that could be classified as practice-based evidence (see https://posproject.org/). Schools wishing to explore use of P2 may wish to consider the best ways to measure the effectiveness of the program. One option is the Values in Action Inventory of Strengths for Youth, which was developed to assess the 24 character strengths from positive psychology and has been translated into multiple languages.